INFLUENCER MARKETING DI ERA DIGITAL: DAMPAK TERHADAP LOYALITAS KONSUMEN DI SOSIAL MEDIA - Putu Sasmita Dewi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2025)
The challenge of measuring the effectiveness of influencer marketing campaigns can pose a significant obstacle for marketers, especially in the digital landscape. Many marketers continue to rely on traditional metrics such as likes and comments, which do not accurately reflect their true impact on consumer behavior and loyalty. This study aims to investigate the relationship between influencer marketing and consumer loyalty on social media, highlighting the need for better evaluation methods. By analyzing secondary literature, consisting of scholarly journals and articles, this study aims to explore how effective influencer marketing can increase consumer engagement and foster long-term brand relationships. Furthermore, it will address the risks associated with influencer authenticity and reputation, which can impact the brand image itself. These findings are expected to provide insights into optimizing marketing strategies and improving business performance in the digital era, ultimately contributing to a deeper understanding of consumer preferences and behaviors in the context of social media marketing.